EMBALAGEM-ANÚNCIO: A MENSAGEM DA PROPAGANDA NO PONTO-DE-VENDA - Alves, Victor Hugo Lima (2009)
This paper approaches packages thru its communicational functions, under the integrated marketing communication perspective. Specifically, it approaches how the package reproduces the message from the advertisement on the point of sale, detailing by the general goal, the description, analysis and systematization of its uses processes as a marketing campaign support, expanding the Integrated Marketing Communication IMC objectives. The methodology is based on the qualitative method, using the descriptive research procedure, and applying as investigative strategies: bibliographical research, documental research and in-depth interview, allowing the conclusion, that under the integrated marketing communication perspective, the expansion of the communicative function of the package allows the advertisement message to be reproduced on the point-of-sale thru the union of elements from television and package messages.(AU)